2020
DOI: 10.1016/j.jmbbm.2019.103426
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Johnson-Cook plasticity model in the finite element simulations of the nanoindentation of the cortical bone.

Abstract: The mechanical behavior of the cortical bone in nanoindentation is a complicated mechanical problem. The finite element analysis has commonly been assumed to be the most appropriate approach to this issue. One significant problem in nanoindentation modeling of the elastic-plastic materials is pileup deformation, which is not observed in cortical bone nanoindentation testing. This phenomenon depends on the work-hardening of materials; it doesn't occur for work-hardening materials, which suggests that the cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…e constitutive equation developed by Johnson-Cook also known as Johnson and Cook model carried out to evaluate the high rate of deformation during the simulation. e model has proven to be very popular and has been used extensively in national laboratories, military laboratories, and private industry to study material behaviors under conditions of large strain and a wide range of strain-rates and temperatures [38,39].…”
Section: Johnson-cook Constitutive Equation Johnson Andmentioning
confidence: 99%
“…e constitutive equation developed by Johnson-Cook also known as Johnson and Cook model carried out to evaluate the high rate of deformation during the simulation. e model has proven to be very popular and has been used extensively in national laboratories, military laboratories, and private industry to study material behaviors under conditions of large strain and a wide range of strain-rates and temperatures [38,39].…”
Section: Johnson-cook Constitutive Equation Johnson Andmentioning
confidence: 99%
“…In this study, we are interested in the elasto-plastic behaviour of articulated truss structures. A simplified linear isotropic strain-hardening model of the Johson Cook type [14] is implemented. Thus, the simplified model is bilinear and characterized by a Young's modulus E and a tangent modulus E T , the yield strength 0 σ , yield stress projection 0 σ ′ (see Figure 1).…”
Section: Selecting a Templatementioning
confidence: 99%
“…the relationship between stress and temperature. The Johnson-Cook model parameters of the bone (Remache et al, 2019) are shown in Table 2.…”
Section: 2constitutive Equation Of Materialsmentioning
confidence: 99%